Study of Influence of Environmental Factors on Deep Shale Creep Properties - Yanchun Wang; Yongyan Wang; Chuanqi Su; Jianguang Li (Shock and Vibration)
In order to study the influence of environmental factors on creep properties of deep shale, a series of creep tests of deep black shales are performed under different environmental conditions, including stress deviation, temperature, and chemical pH value. The influence of these conditions on creep properties of deep shale is studied. The results show that the creep and creep rate of shale will grow with the increase of temperature, stress difference, and acidity-alkalinity. We get nonlinear creep model of deep shale when pH = 4 and T = 30°C. The critical stress difference of deep shale is no larger than 31.04 MPa when the chemical pH value is 4 and the temperature is 30°C. By scanning shale after corrosion, we know that the effects of chemical pH value on the creep characteristics are mainly determined by the feldspar dissolution and corrosion caused by chemical action. Our work has important theoretical significance and practical value for evaluating rock engineering stability.